Monitoring Shoreline Change Using Medium Resolution Multi-Temporal Satellite Imagery: A Case Study of Keta, Ghana - Quashigah, P-N.J. (University of Ghana, 2011)
Shoreline change analysis provides important information upon which most coastal zone management and intervention policies rely. Such information is however mostly scarce for very large and inaccessible shorelines mostly due to expensive field work. This study investigated the reliability of medium resolution satellite imagery for mapping shoreline positions and for estimating historic rate of change. Both manual and semi-automatic shoreline extraction methods for multi-spectral satellite imageries were explored. Five shoreline positions were extracted for 1986, 1991, 2001, 2007 and 2011 covering a medium term of 25 years period. Two additional shoreline positions for 2010 and 2011 were extracted and used for accuracy assessment. Rates of change statistics were calculated using the End Point Rate and Weighted Linear Regression methods. Approximately 283 transects were cast at simple right angles along the entire coast at 200m interval. Uncertainties were quantified for the shorelines ranging from ±4.1m to ±5.5m accuracy of mapping the shoreline at 15m resolution estimated to be ±11m. The results show that the Keta shoreline is a very dynamic feature with average rate of erosion estimated to be about 2m/year ±0.44m. Individual rates along some transect reach as high as -16m/year near the estuary and on the east of the Keta Sea Defence site. The study confirms earlier rates of erosion calculated for the area and also reveals the influence of the Keta sea defence on erosion along the eastern coast of Ghana. The research shows that shoreline change can be estimated using medium resolution satellite imagery.